Association of early aspirin use with 90-day mortality in patients with sepsis: an PSM analysis of the MIMIC-IV database - Huang, Chunsheng; Tong, Qiaoling; Zhang, Wenyuan; Pan, Zhihao (Frontiers in Pharmacology, 2025)
ObjectiveIn addition to its antiplatelet and anti-inflammatory properties, aspirin inhibits bacterial proliferation directly. The potential benefits of aspirin may enhance the prognosis for sepsis patients. However, little is known about the effects of early aspirin administration. This study aimed to examine the correlation between the administration of aspirin at an early stage and the 90-day mortality rate among sepsis patients.MethodsIn order to distinguish between septic patients who received early aspirin treatment and those who did not, queries were conducted on the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The principal metric utilized was 90-day mortality. We determined the association between early aspirin use and 90-day mortality using multivariate Cox regression, and propensity score matching (PSM) was utilized to validate our findings. The analyses of the subgroups have been completed.ResultsOur analysis comprised 28,425 septic patients, of whom 7,568 (26.6%) received aspirin within 24 h of intensive care unit (ICU) admission. The aspirin users group had a lower 90-day mortality than the aspirin nonusers group [1,624 (21.8%) vs. 2,035 (27.3%), P < 0.001]. The logistic regression showed that early aspirin use was associated with a lower 90-day mortality (OR, 0.74, 95% CI, 0.69–0.80, P < 0.001). K-M curve analysis showed that the 90-day mortality of the aspirin users group was significantly lower than that of the aspirin nonusers group (P < 0.001). Subgroup analysis revealed comparable relationships between early aspirin use and 90-day mortality among individuals.ConclusionIn conclusion, early aspirin use was associated with decreased in-hospital and 90-day mortality in septic patients, emphasizing the significance of early aspirin use administration in the ICU.